Histoplasma capsulatum-Induced Cytokine Secretion in Lung Epithelial Cells Is Dependent on Host Integrins, Src-Family Kinase Activation, and Membrane Raft Recruitment - Maza, Paloma K.; Suzuki, Erika (Frontiers in Microbiology, 2016)
Histoplasma capsulatum var. capsulatum is a dimorphic fungus that causes histoplasmosis, a human systemic mycosis with worldwide distribution. In the present work, we demonstrate that H. capsulatum yeasts are able to induce cytokine secretion by the human lung epithelial cell line A549 in integrin- and Src-family kinase (SFK)-dependent manners. This conclusion is supported by small interfering RNA (siRNA) directed to alpha 3 and alpha 5 integrins, and PP2, an inhibitor of SFK activation. siRNA and PP2 reduced IL-6 and IL-8 secretion in H. capsulatum-infected A549 cell cultures. In addition, alpha 3 and alpha 5 integrins from A549 cells were capable of associating with H. capsulatum yeasts, and this fungus promotes recruitment of these integrins and SFKs to A549 cell membrane rafts. Corroborating this finding, membrane raft disruption with the cholesterol-chelator methyl-beta-cyclodextrin reduced the levels of integrins and SFKs in these cell membrane domains. Finally, pretreatment of A549 cells with the cholesterol-binding compound, and also a membrane raft disruptor, filipin, significantly reduced IL-6 and IL-8 levels in A549-H.capsulatum cultures. Taken together, these results indicate that H. capsulatum yeasts induce secretion of IL-6 and IL-8 in human lung epithelial cells by interacting with alpha 3 and alpha 5 integrins, recruiting these integrins to membrane rafts, and promoting SFK activation.